Ascertaining the Growth Performance, Ileal Gut Morphology, Gastro-Intestinal Development and Viability of Broiler Chicken Fed L-Methionine (L-Met) Supplemented Diet - Akter, N.; Islam, M.S.; Hossain, M.A.; Jahan, I.; Ahmad, M.H.; Hossain, M.M. (International Journal of Poultry Science, 2020)
Objective: The study was conducted to investigate the productivity of broiler fed diet supplemented with L-methionine. Materials and Methods: Day-old broiler chicks (n = 216: Cobb500) were reared from day 1-33 in the battery cages. The chicks were distributed randomly into four treatments, i.e., D0 (DL-Met), D1 (0.20% L-Met), D2 (0.25% L-Met) and D3 (0.30% L-Met) in a CRD. Each treatment was replicated 6 times with 9 birds per replicate. Chicks were fed commercial starter diet ad libitum up to 2 weeks . After that, test diets were supplied throughout the trial period (15-33 day). All the formulated diets were iso-caloric and iso-nitrogenous. Data were collected for feed intake (FI), live weight (LW), feed conversion ratio (FCR) and livability. Visceral organs and ileal samples were collected on day 33 to assess the gut morphology and gastro-intestinal development of broiler. Results: The data revealed that FI (p0.05) differences were found in the visceral organ weights (small intestine, proventriculus, gizzard, liver, heart, spleen and bursa) of broilers except for pancreas, which was found higher (p